Proteins sharing PNPLA domain, a new family of enzymes regulating lipid metabolism - Baulande, Sylvain; Langlois, Clotilde (M.S. Médecine sciences, 2010)
Genome sequencing technologies led to tremendous breakthrough in biology uncovering numerous genes unknown so far and thus opening the field of deep investigations to understand their associated biological functions. As a matter of fact, functional genomics have been progressively replacing sequence genomics with as a main objective to yield insight into cellular physiology. Recently, an emerging group of genes coding for proteins bearing a common domain termed patatin (PNPLA domain) have been discovered. Members of this new enzymatic family displaying lipase and transacylase properties appeared to have major roles in the regulation of lipid metabolism. The aim of this review is to make an overview on the latest discoveries concerning this new family of proteins and their relationship with lipid metabolism, physiology of mammals and their potential involvement in human pathology.